Per un commento a Con il sole nel muro grande di casa. Da Umana gloria di Mario Benedetti - Crocco, Claudia (L'ospite ingrato, 2021)
This essay aims to comment Con il sole nel muro grande di casa, a poem taken from Umana gloria (2004) by Mario Benedetti. In addition to explaining the most difficult lines of the text, the article points out stylistic and thematic recurrences with other poems of Umana gloria. The text analysis is also based on the reading of the Bachelor Thesis that Benedetti dedicated to Michelstaedter (only recently available for reading, and still unpublished), which is useful to clarify the poetics of his works, in particular of Umana gloria.